IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Nursaidatina Amran - Amran, Nursaidatina (2015)
Article on: Article 1: “An Investigation of Using Video vs. Audio for Teaching Vocabulary” Article 2: “Iranian Teachers’ Perspective of the Implementation of Audiovisual Devices in Teaching”